P-524 Bi-allelic CFAP61 variants cause male infertility in humans and mice with severe oligoasthenoteratozoospermia. (30th June 2022) - Hu, T; Meng, L; Tan, C; Luo, C; He, W B; Tu, C; Zhang, H; Du, J; Nie, H; Lu, G X; Lin, G; Tan, Y Q
Abstract: Study question: Are mutations in cilia and flagella-associated protein 61 ( CFAP61 ) associated with human male infertility? Summary answer: Bi-allelic variants ([NM_015585.4: c.1654C>T (p.R552C) and c.2911G>A (p.D971N), c.144-2A>G and c.1666G>A (p.G556R)] in CFAP61 were identified as contributory genetics factor in severe oligoasthenoteratozoospermia (OAT). What is known already: Cfap61 knockout mice were infertile due to multiple morphological abnormalities of the sperm flagella (MMAF). However, so far there is no direct evidence that mutations of CFAP61 cause OAT and male infertility. Study design, size, duration: Variant screening was performed by whole-exome sequencing (WES) from 325 infertile patients with OAT and 392 fertile individuals. A knockout mouse model was generate to confirm the candidate disease-causing gene, intracytoplasmic sperm injection (ICSI) was used to evaluate the efficiency of clinical treatment. Participants/materials, setting, methods: A total 325 OAT-affected patients and 392 men with normal fertility were recruited from China. WES was performed, followed by Sanger sequencing validation. In silico bioinformatics predictions and in vitro functional analyses were performed to evaluate the impacts of candidate disease-causing variants. Hematoxylin and eosin (H&E) staining, electron microscopy, and immunofluorescence assays were performed to evaluate the sperm morphology. Two OAT-affected men with CFAP61 variants were treated by ICSI, and pregnancy outcomes were followed. Main results and the role of chance: We identified bi-allelic CFAP61 variants [NM_015585.4: c.1654C>T (p.R552C) and c.2911G>A (p.D971N), c.144-2A>G and c.1666G>A (p.G556R)] in two (0.62%) of the 325 OAT-affected men. In silico bioinformatics analysis predicted that all four variants were deleterious, and in vitro functional analysis confirmed the deleterious effects of the mutants. Notably, H&E staining and electron microscopy analyses of the spermatozoa revealed multiple morphological abnormalities of sperm flagella, the absence of central pair microtubules, and mitochondrial sheath malformation in sperm flagella from man with CFAP61 variants. Further immunofluorescence assays revealed markedly reduced CFAP61 staining in the sperm flagella. In addition, Cfap61 -deficient mice showed the OAT phenotype, suggesting that loss of function of CFAP61 was the cause of OAT. Two individuals accepted ICSI therapy using their own ejaculated sperm, and one of them succeeded in fathering a healthy baby. Limitations, reasons for caution: Limitations include the lack of in vivo data from the one of patients, and the exact molecular mechanism should be further investigated. Wider implications of the findings: Our findings indicate that CFAP61 is essential for spermatogenesis and that bi-allelic CFAP61 variants lead to OAT and male infertility in humans and mice. In addition, our results show that ICSI treatment can be recommended for CFAP61 -related OAT. Trial registration number: not applicable